Relationship between health literacy, health fatalism and attitudes towards cancer screenings: latent profile analysis - Uncu, Fatos; Evcimen, Hasan; Ciftci, Necmettin; Yildiz, Metin (Bmc, 2025)
BackgroundThe aim of this study is to examine the relationship between health literacy, health fatalism and attitudes towards cancer screening using latent profile analysis (LPA).MethodsThis study was conducted in a cross-sectional descriptive design between December 2023- December 2024. The study was conducted with 1262 adult individuals living in a province in eastern Turkey.ResultsAs a result of LPA, Class 1 was named as High Health Awareness and when the indicators in Class 1 were analyzed, it was found that health literacy and attitude towards cancer screenings were high and health fatalism was low. Class 2 is labeled as Low Health Awareness and when the indicators in this class are examined, it is determined that health literacy and attitude towards cancer screening are low and health fatalism is high.ConclusionsIn our study, individuals were divided into two classes as High Health Awareness and Low Health Awareness according to the level of health awareness; in the first class, health literacy and attitudes towards cancer screenings were high and health fatalism was low; in the second class, health literacy and attitudes were low and health fatalism was high.
Keywords: Health literacy; Health fatalism; Cancer Screenings; Attitude; Latent profile analysis